Program Kegiatan Posyandu Balita untuk Menciptakan Generasi Sehat dan Cerdas - Qurrotul Aini; Conny Dian Sumadi; Machful Indrakurniawan (Lembaga Citra Pustaka, 2024)
This study ams to the posyandu toddler program in buddagan village 1,larangan luar district,pamekasan regency in an effort to improve basic healty services for toddlers.this study uses aqualitative approach with data collections techiques through observations,and interview,amd documentations.observations,and interviews with a number of informants data analysis drawing conlusions.the results of the study showed several problems,such as low public awaresness of the importance of toddler health and nutrition care,and lack of recording of posyandu activities.however the implementation of the posyandu toddler program has been good becaice it provides basic health services such as weighing,measuaring heightand providing additional food every month.the obstacles faced inluce the location of the posyandu which is far from some residents’homes and low community parcipations.in conclusion,the posyandu toddler program in buddagan village 1 shows that although this progrsm has been running according to procedures and providing good service,there are stiil several aspects that need to be improved.community prcipations and completeness of data need to be improved to achieve better effectiveness.